ANALYSIS OF IMPLEMENTATION OF SIMDA BMD BOARD OF FINANCIAL AND ASSET MANAGEMENT BANDUNG CITY - Silviana,; Rakhman, Syaid; Rohman, Yeni (International Journal of Psychosocial Rehabilitation, 2020)
Even though SIMDA BMD has been used, there are still weaknesses in the system. The study aims to analyze the implementation of SIMDA BMD BPKA Bandung City Government. The analytical approach uses the information system success model DeLone and McLean. This research uses a quantitative descriptive approach. Data collection techniques using questionnaires, the number of respondents as many as ten employees operating SIMDA BMD. The results showed the implementation of SIMDA BMD in the very good category, but still found some weaknesses including not having a specific application to fix system failures; in terms of the timeliness of sending reports is still not optimal is still not optimal; employees do not always access SIMDA BMD more than one hour every day; user time efficiency in using SIMDA is still not optimal.